The phase structure of the Polyakov--quark-meson model beyond mean field - Herbst, Tina; Pawlowski, Jan M.; Schaefer, Bernd-Jochen (Arxiv, 2010)
The Polyakov-extended quark-meson model (PQM) is investigated beyond mean-field. This represents an important step towards a fully dynamical QCD computation. Both the quantum fluctuations to the matter sector and the back-reaction of the matter fluctuations to the QCD Yang-Mills sector are included. Results on the chiral and confinement-deconfinement crossover/phase transition lines and the location of a possible critical endpoint are presented. Moreover, thermodynamic quantities such as the pressure and the quark density are discussed.